Building an adaptive selling capability model to improve MSMEs marketing performance - Saputra, Murry Harmawan; Ariningsih, Endah Pri (Diponegoro International Journal of Business, 2025)
This study aims to develop a conceptual model of Adaptive Selling Capability (ASC) to improve marketing performance in Micro, Small, and Medium Enterprises (MSMEs) in Central Java, Indonesia. MSMEs have a very important role in the national economy, but there are still many obstacles in sales strategies to meet diverse customer needs and dynamic market conditions. Grounded in the Dynamic Capability Theory, this study explores how ASC affects Value-Based Selling (VBS) and Sales Interaction Quality which in turn impacts the marketing performance of MSMEs. Using a survey method with 242 MSME respondents from various sectors, the data was analyzed using Structural Equation Modeling (SEM-AMOS). The results show that ASC has a positive effect on VBS and SIQ, both of which significantly improve the marketing performance of MSMEs. This study fills a gap in the literature that shows mixed results regarding the influence of ASC. The practical implications of this research underscore the importance of improving adaptive selling capabilities and value-based communication from MSME actors to customers. MSMEs also need to be encouraged to adopt technology in their sales strategies to improve their competitiveness. This research contributes to the marketing and management literature by expanding the application of Dynamic Capability Theory in the context of MSMEs.